Relationship Between Hospitality Services and Tourist Satisfaction in Nepal - Silwal, Mod Nath; Maharjan , Gautam (Nepalese Journal of Hospitality and Tourism Management, 2026)
This study aims to examine the impact of hospitality service on tourist satisfaction in Nepal. This study uses a quantitative approach. A descriptive research design was used to characterize the data. In contrast, a causal-effect research design was adopted to determine the effect of hospitality service on tourist satisfaction in Nepal. For the tourist destinations in Nepal, such as Kathmandu, Pokhara, Ghorepani, Ghandruk, Lumbini, and Chitwan, a judgmental sampling technique was used to obtain 404 final responses via a 5-point Likert-scale questionnaire. This study employed descriptive statistics, correlation analysis, and regression analysis. It was found that hospitality services have a significant positive impact on foreign tourists’ satisfaction in Nepal. It was concluded that hospitality service is a major factor for tourist satisfaction in Nepal. However, this study has covered only a few destinations in Nepal. The novelty of this study is that it offers the first broad quantitative proof that hospitality causally affects foreign tourist satisfaction in Nepal, empirically validating this link across six key destinations beyond basic description.